The Overdense Environments of WISE-Selected, Ultra-Luminous, High-Redshift AGN in the Submillimeter - Jones, Suzy F. (Frontiers in Astronomy and Space Sciences, 2017)
The environments around WISE-selected hot dust obscured galaxies (Hot DOGs) and WISE/radio-selected active galactic nuclei (AGNs) at average redshifts of $z = 2.7$ and $z = 1.7$, respectively, were found to have overdensities of companion submillimetre-selected sources. The overdensities were of $\sim 2 - 3$ and $\sim 5 - 6 $, respectively, compared with blank field submm surveys. The space densities in both samples were found to be overdense compared to normal star-forming galaxies and submillimetre galaxies (SMGs). All of the companion sources have consistent mid-IR colours and mid-IR to submm ratios to SMGs. Monte Carlo simulations show no angular correlation, which could indicate protoclusters on scales larger than the SCUBA-2 1.5\,arcmin scale maps. WISE-selected AGNs appear to be good indicators of overdense areas of active galaxies at high redshift.